The Relationship between Macroeconomic Factors and the Level of Non-Performing Loans (NPLs) of Commercial Banks in Vietnam / Nguyen Huu Quang, Nguyen Xuan Nhi - Nguyen, Huu Quang
The purpose of this article is to estimate the effects of macroeconomic factors on the the level of non-performing loans (NPLs) of Commercial Banks in Vietnam by using econometric model on the commercial banks for the 2004-2015 periods. It is obvious that banks have to take risk all the time and there are three major risks, including credit risk, market risk and operational risk (Perez, 2014). Credit risk is one of the most important kinds of risk in commercial banking sector. The Basel Committee on Banking Supervision defines credit risk as the potential that a commercial bank borrower, or counter party, will fail to meet its payment obligations regarding the terms agreed with the commercial bank (Perez, 2014). This study also finds that NPLs are not the problem of the commercial bank but the government must consider it carefully. It is clear that commercial banks must have a right thought about NPLs as well as analyze the reasons to give the reasonable solutions to solve the issue. In addition, this study also points out that if the commercial banks in Vietnam try to hide the bad debt, the real status of the commercial bank will be reflected unexpectedly, leading to the results will affect to the capital supply of national economics.